Pengaruh Loyalitas Kerja, Lingkungan Kerja dan Komunikasi Terhadap Organizational Citizenship Behavior Tenaga Non-Medis Rumah Sakit PKU Muhammadiyah Sruweng - Putri Ayu , Nikmah; Irfan, Helmy (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2023)
This research aims to determine the influence of work loyalty, work environment and communication on organizational citizenship behavior in non-medical personnel at PKU Muhammadiyah Sruweng Hospital, Kebumen Regency. The population and sample in this study were all non-medical employees at the PKU Muhammadiyah Sruweng Hospital, totaling 50 people. The data analysis method uses validity, reliability and multiple linear regression analysis. The research results show that loyalty, work environment and communication have a positive and significant effect on Organizational Citizenship Behavior both partially and simultaneously